Estimation of the Potential Runoff Quality Improvement as a Result of Applied Green Infrastructure Measures in a Hungarian Town - Hancz, Gabriella; Biró, János (International Journal of Engineering and Management Sciences, 2018)
Green infrastructure measures improves the quality of surface and subsurface waters along with increasing the water balance on the town level. The aim of the study is to estimate the potential runoff quality improvement by applying stormwater BMP-s along traffic roads in the town. This is of high priority in the aquifer protection area where runoff water may infiltrate into the aquifer carrying pollutants from the surface. Estimations are applied: first we determine the surface of traffic roads, then estimate the quantity of different kinds of pollutants accumulated on the surface and thirdly we estimate the expected performance of the applied green infrastructure elements based on findings in the literature. We determine the impervious urban surface area associated with transport-related functions within the protected drinking water recharge area using GIS technic using orthophotos. We estimate the expected reduction of runoff pollution assuming that stormwater BMP-s are applied in the area. The overall goal is to make the significance of diffuse pollution more obvious and enhance drinking water protection through taking diffuse pollution into consideration.